PELATIHAN DAN PENGEMBANGAN SDM, BUDAYA ORGANISASI DAN TIPE KEPEMIMPINAN TERHADAP KOMPETENSI SDM DI KOTA MEDAN - Fatimah Pohan; Joan Berlin Damanik; Corinna Wongsosudono; Nirwana Br. Bangun; Arasy Ayu Setiamy (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The number of human resources absorbed in the world of work is increasing, but the quality or quality of our human resources is low, because the training and development of human resources to improve competence has not been carried out optimally, so that some existing human resources do not have good competence, so they have not been looked at in well-known companies. in addition, organizational culture affects the ability of human resources. Some of the existing human resources have not been able to adapt well to the company's organizational culture, so that their competencies do not appear well, because there are some existing companies that still apply a work culture that is not liked by some workers, so that their competencies are not maximized and have not convinced management. The type of leadership also affects competence, where there are few companies that have this type of leadership that tends to distrust subordinates, where this type of leadership tends to affect the abilities and competencies of subordinates, where the competence of subordinates is not appreciated and affects the performance of subordinates and the company's overall performance. The research method used is descriptive quantitative using multiple linear regression analysis using SPSS 25. The population of this study is human resources who have worked in several companies throughout the city of Medan, amounting to 100 people/person, where the sampling technique in this study uses technique of the census method, with a sample of 100 HR people who have worked in several companies throughout the city of Medan through the distribution of questionnaires conducted using an online method. The results of the study which were based on the hypothesis partially and simultaneously stated that the variables of HR training and development, organizational culture and leadership type had an effect on the HR competency variables working in companies throughout the city of Medan.